DEVELOPMENT OF A PEOU-BASED BAKERY MODULE AND ACTUAL SYSTEM USE FOR STUDENTS WITH DISABILITIES AT SLB NEGERI 2 BANTUL - Habibah Marie Curie; Endang Mulyatiningsih; Icha Fatwasauri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The purpose of this study is to improve the understanding and practical skills of PWD students. Learning at SLB Negeri 2 Bantul still focuses on direct presentation methods without the support of interactive modules that are easy to use and access by students. This condition creates a mismatch between the need of practical learning and the availability of media that suits the characteristics of PWD students. This study uses a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through observation, interviews, and questionnaires. The instrument used was a validated questionnaire by material experts and media experts. The results of the validity test for the feasibility of the material experts obtained a score of 89% with a very feasible category, while the media experts obtained a score of 98% with a very feasible category. The results of the effectiveness test on students obtained a t-test score of 21.0 which indicates that there is a significant difference in the use of the PEOU-based bakery practice module and the use of the actual system. Therefore, the developed module is proven to be effective in improving PWD students learning outcomes in the bakery practice material